Tobacco control in Zimbabwe and the WHO Framework Convention on Tobacco Control (WHO FCTC): State of Affairs - Rusere, Chipo (School of Economics, 2020)
Zimbabwe’s government has, in the past, expressed opposition to the WHO Framework Convention on Tobacco Control (WHO FCTC). Since the country’s ratification of the WHO FCTC in 2014, the government has put in place financial incentives to promote tobacco production, contrary to the WHO FCTC. The conflicting signals, coupled with seemingly contradictory actions, have raised doubts about the country’s true intent when it ratified the treaty. This thesis assesses the implementation of Zimbabwe’s current tobacco-control legislation, through a synthesis of information from semi-structured interviews with key informants involved in tobacco control in the country. This is supplemented by a situation analysis examining government efforts to align existing tobacco-control legislation with the WHO FCTC. Results show that Zimbabwe’s existing tobacco-control legislation was biased because of tobacco-industry interference during the early stages of the drafting of the bill. There is currently no prioritisation of tobacco-control efforts by government, even after their ratification of the WHO FCTC. As of February 2019, government actions run counter to the supply-reduction measures and recommendations stipulated in the WHO FCTC and associated policy guidelines. Indications are that the government’s ratification of the treaty does not represent a weakening of the government’s resolve to promote tobacco production and protect the country’s tobacco farmers. Accession to the WHO FCTC appears to have been an opportunity to present the country’s concerns, particularly those relating to the supply-side provisions of the WHO FCTC, and possibly disrupting WHO FCTC efforts to limit tobacco-industry interference and advance global tobacco-control efforts.